Pendampingan dan Pelatihan Komprehensif Transformasi Edukasi Pengetahuan Tanaman Herbal Tradisional Menjadi Solusi Kesehatan Kontemporer di Desa Junjangan Kecamatan Batang Tuaka Provinsi Riau - M. Ilyas; Kafrawi Kafrawi; Mulyadi Mulyadi; Abdul Syahid; Fahrina Yustiasari Liriwati (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This comprehensive mentoring and training program is designed to transform the traditional knowledge of the community in Junjangan village, Batang Tuaka District about herbal plants into contemporary health solutions. Through a comprehensive educational approach, this program aims to empower people to use herbal plants as an effective and natural alternative treatment. This mentoring includes identification of local knowledge, practical training and ongoing support to ensure appropriate and sustainable implementation. The results of this program show a significant increase in the community's understanding and skills in processing and utilizing herbal plants for health. Apart from that, this program also contributes to the preservation of traditional knowledge and improves the welfare of the people of Junjangan village, Batang Tuaka District, Riau Province. This article provides in-depth insight into the impact of the program as well as the challenges faced in this transformation process.